Economic policy in ancient India - Nath, Ravindra (Delhi, 2007)
No civilization ran without an eminent strategic economy, but to trace out the economic scheme of civilizations by gone into oblivion is an uphill task. This book is a unique listimony of such great toil and of enormous historical understanding. Economic policy in ancient india as cultural them has been well discovered and analyzed with the help of the hoard of scriptures. A unique treatise on this issue. Failtless scholars.
Keywords: Economic policy-India